FRACTURE AND BEDDING PLANE CONTROL ON GROUNDWATER FLOW IN A CHALK AQUITARD - Weiss M.; Rubin Y.; Adar E.; Nativ R. (My University, 2006)
Shallow groundwater in the northern Negev desert of Israel flows preferentially through a complex system of discontinuities. These discontinuities intersect what would otherwise be a massive, low-conductivity, high-porosity Eocene chalk. Vertical fractures and horizontal bedding planes were observed and mapped along approximately 1,200 m of scanline, 600 m of core and 30 two-dimensional trace planes. A bimodal distribution of size exists for the vertical fractures which occur as both single-layer fractures and multi-layer fractures. A bimodal distribution of log transmissivity was observed from slug tests conducted in packed-off, vertical intervals within the saturated zone. The different flow characteristics between the horizontal bedding planes and vertical-type fractures appear to be the cause of the bimodality. Two distinct conceptual models (discrete fracture network) were developed based on the fracture orientation, size, intensity and transmissivity statistics derived from field data. A correlation between fracture size and hydraulic aperture was established as the basis for calibrating the simulated model transmissivity to the field observations. This method of defining transmissivity statistically based on prior information is shown to be a reasonable and workable alternative to the usual conjecture approach towards defining transmissivity in a fractured-rock environment.
Keywords: GROUNDWATER; FRACTURES; CHALK; ISRAEL; MODELING; GEOSTATISTICS; Eocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен